2008
DOI: 10.1097/01.hcr.0000311511.23849.35
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Insights Into a Nurse-Delivered Motivational Interviewing Intervention in the Outpatient Cardiac Rehabilitation Setting

Abstract: Pragmatic insights into a nurse-delivered motivational interviewing intervention in the outpatient cardiac rehabilitation setting ABSTRACT PURPOSE: Despite an increasing interest in motivational interviewing as a strategy to facilitate behavior change in people with cardiovascular disease, its use specifically in cardiac rehabilitation (CR) appears minimal. Therefore, it is unclear if the clinical method of motivational interviewing requires modification for the CR population, in which it could be argued that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Patients in a cardiac rehabilitation study rated “health” as one of their most important values [42]. Endorsing the value “health” predicted improved physical activity among firefighters [28].…”
Section: Introductionmentioning
confidence: 99%
“…Patients in a cardiac rehabilitation study rated “health” as one of their most important values [42]. Endorsing the value “health” predicted improved physical activity among firefighters [28].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 gives an overview of empirical studies using motivational interviewing in clients at risk of or with established CHD or heart failure. Of these six studies, one reported the use of motivational interviewing alone in outpatient cardiac rehabilitation (Everett et al. 2008), one to improve heart failure self‐care (Riegel et al.…”
Section: Resultsmentioning
confidence: 99%
“…[5] The precise mechanism of behavior change is not well understood, however the most influential features of MI that contribute to modifying health habits include collaborative spirit and ability to motivate a patient. [4,13,22,23] Previous research findings demonstrate how nursing students embodied MI spirit and motivation in their patient encounters and this is significant because clinician spirit and patient motivation are considered interdependent catalysts for behavior change. [13,14] In this research, spirit and motivation contributed to patients' perceptions of a collaborative alliance with the nursing students that was different from the information-focused and expert-driven experiences with 'typical' health providers.…”
Section: Discussionmentioning
confidence: 99%